Current and Future Use of ICT for Patient Care and Management in German Acute Hospitals - Hübner, U.; Sellemann, B. (Methods of Information in Medicine, 2005)
Objectives: This study aimed at gaining comprehensive information on the current status of patient care and management applications used in German acute hospitals. Since the degree of ICT coverage in hospitals depends on the attitude of the key decision makers we also wanted to capture their plans and priorities and herewith try to predict future use.Methods: We therefore conducted a nation-wide survey including all acute hospitals in Germany in which two questionnaires were mailed to each hospital, one to the nursing managers, the other to the hospital managers.Results: Six hundred hospitals participated in the survey which corresponds to an overall response rate of 27.6%. Accounting (84%) was found to be the most prevalent management module. Rostering was implemented in every second hospital. For clinical applications laboratory systems ranked first (69%). Ordering systems were used in nearly every second hospital. Nineteen percent of the hospitals reported employing an electronic patient record, 7% a nursing documentation system. Ranked by their priorities ordering systems hold the first position and care planning the last position. According to their plans, hospital managers, not nursing managers, intend to introduce nursing documentation. In contrast, nursing managers favor ordering and rostering for the near future.Conclusions: There is still a preponderance of management-oriented systems in German hospitals, yet clinical applications, in particular those supporting communications, will gain ground. The future of documentation systems is unclear, unless they not only provide statistical data for the management but support the clinical process properly.
Keywords: Hospital information system; patient care; computerized patient record; hospital administration; data collection